The influence of communication and work discipline on the performance of employees of Duri Kosambi Cengkareng Village Office, West Jakarta - Siti Hajir (Keynesia : International Journal of Economy and Business, 2023)
This study aims to determine the influence of communication and work discipline on the performance of employees of Duri Kosambi Village Office, Cengakareng, West Jakarta. So the objectives to be achieved in this study are to find out how much influence communication has on the performance of employees of Duri Kosambi Cengkareng Village Office, West Jakarta. To find out how much influence work discipline has on the performance of employees of Duri Kosambi Village Office, Cengkareng, West Jakarta. To find out how much influence communication and work discipline together have on the performance of employees of Duri Kosambi Village Office, Cengkareng, West Jakarta. The approach used in this study is a quantitative approach with Likert scale, linear regression analysis and coefficient of determination analysis used to determine how much influence a variable has on other variables. The population of this survey is employees of Duri Kosambi Village Office, Cengkareng, West Jakarta, totaling 53 respondents. Data processing in this study used SPSS (Statistic Package for the Social Sciens) software program version 23.00. The results of this study show that communication affects employee performance at Duri Kosambi Cengkareng Village Office, which is 44.4%. Work discipline affects the performance of employees at the Duri Kosambi Cengkareng Village Office, which is 58.2%. Communication and work discipline jointly affect the performance of employees at the Duri Kosambi Cengkareng Village Knator, which is 50,074.